The effect of Ag or Au addition on electro- and magnetoresistive properties of Ni80Fe20 thin films: 11 - Lohvynov, A.M.; Pazukha, I.M.; Pylypenko, O.V.; Dolgov-Gordiichuck, S.R.; Panchoshnyi, O.O.; Khyzhnya, Ya.V. (Physics and Chemistry of Solid State, 2024)
The electrophysical and magnetoresistive properties of permalloy Ni80Fe20 (Py) and Py64Ag36 and Py64Au36 thin films prepared by the electron-beam sputtering are presented. The effect of the addition of a third element (Ag or Au) on the resistivity, temperature coefficient of resistivity and magnetoresistance of permalloy films has been described. The structural, electrophysical and magnetoresistive properties of the investigated samples showed a strong dependence on the annealing temperature.